Needs Assessment about Adolescent Reproductive Health Education for Students - Eko Winarti; Fauziah Laili; Teguh Pramono; Sondang Sidabuntar (EMBRIO, 2021)
Adolescent Reproductive Health (ARH) problems are currently increasingly concerning, this is due to the low knowledge of adolescents about ARH. Increasing knowledge of adolescents about ARH can be done through adolescent health education. Research objectives to see the needs of students about adolescent health education. Research design using cross-sectional. Consists of all students at the Kota Kediri. The sample of some students was 35 respondents using the cluster random sampling technique. Data were collected by questionnaires and interviews. Data analysis using the statistical test of rank spearman. The results showed that almost all respondents had low knowledge (85.7%), mostly good psychological conditions (71.4%), almost all of the level needs assessment of ARH education was high (82.9%). The ARH education method attracted the most questions and answers (88%). ARH media education is the most popular video (86%). The most popular ARH education material was how to care for organs (95%). Almost all of the presenters of ARH education chose health workers (92%). There is a significant relationship between knowledge and the need level of the ARH education assessment, but there is no relationship between psychological conditions and the assessment of the needs of the ARH education level at Kota Kediri in 2021. Based on this research it can be denied that ARH education is needed by students and in delivering the program. ARH education in higher education is adjusted based on student needs.